PENGARUH UNSUR-UNSUR SISTEM PENGENDALIAN MUTU KAP TERHADAP KUALITAS HASIL AUDIT - SINGGIH PERMANA, HENDRA; DUDY SETYAWAN, MADE (Jurnal Akuntansi AKUNESA, 2018)
ABSTRACT This study aims to determine the effect of the elements of Public Accountant Firm?s quality control system on the quality of audit results. The population in this study is Public Accountant Firm in Surabaya, with samples of this study are being chosen by using nonprobality sampling method. The analyze method in this study uses Structural Equation Modeling (SEM) with Partial Least Square approach using Warp PLS 6 test tool. The results of the study indicate that the elements of leadership responsibility, acceptance and sustainability of relationships with clients, and the conduct of audits have an influence on the quality of audit results. While the elements of the provisions of professional ethics, human resources, and monitoring have no effect on the quality of audit results. KeyWords: Quality Control System, Auditing, Public Accountant Firm, Audit .Quality